Revolutionizing cell-based protein: Innovations, market dynamics, and future prospects in the cultivated meat industry - Abdul Samad; SoHee Kim; Chan Jin Kim; Eun-Yeong Lee; Swati Kumari; Md Jakir Hossain; AMM Nurul Alam; Ayesha Muazzam; Uzma Bilal; Young-Hwa Hwang; Seon-Tea Joo (Journal of Agriculture and Food Research)
The world's population is proliferating, and the growing population needs more food resources. Meat is one of the essential dietary components for humans, but the available meat resources are insufficient to fulfill consumers' demands. In this scenario, the meat alternative could be a sustainable resource for fulfilling the meat demand. Cultured meat is one of the best meat alternatives and also has the potential to fulfill the meat demand of the growing population. Cultured meat is produced by cultivating animal stem cells and allowing them to undergo a growth and division process that closely mimics the natural cellular development inside living organisms. The primary reasons behind cultured meat production are to minimize the environmental effect by reducing methane emissions, to minimize the meat cost so it will be economical for the consumer, and to provide antibiotic-free meat. This review explains cultured meat production and new technologies being introduced to create opportunities to improve the overall production of cultured meat. It also explores the cultured meat sector's market opportunities and challenges to the cultured meat industry.